PENGGUNAAN JENIS LARO TERHADAP PERBEDAAN ORGANOLEPTIK DAN pH NIRA SIWALAN - Ismawati Ismawati; Ratih Yuniastri (Journal of Food Technology and Agroindustry dipublikasikan oleh Universitas Wiraraja, 2019)
Laro is one of the natural preservatives of siwalan juice made from tree bark which is mixed after being roughly ground. This research used laro bark of cashew trees and tree bark. The aim of the study was to determine the quality of siwalan juice using different types of laro. The treatment in the study was the use of laro types including siwalan juice without the use of laro, siwalan nira using laro tree bark and siwalan nira using laro from the skin of cashew trees. Of the three treatments, different pairs of tests were carried out on taste, color, aroma and turbidity and pH test. The results showed that there were differences in taste, color, aroma, turbidity and pH of siwalan juice from each treatment. The best treatment for the quality of siwalan sap is by using cashew laro.